Peningkatan Pemahaman Materi Teks Nonfiksi Menggunakan Media Sway Office 365 - Nursyaidha Nursyaidha (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
During a pandemic like this, all efforts will be made of course in accordance with the procedures in the education system in terms of the learning process carried out by a remote system using an online network. Since learning from home (BDR) has been implemented, face-to-face opportunities with students do not occur, while knowledge transfer must continue. This research is based on problems conducted online in Class IV SDN Sawunggaling VII/388 as follows: (a How are teacher and student activities in an effort to increase student understanding of non-fiction text material for Indonesian language lessons theme 5 using Sway Office 365 media (b) What are the results learning in an effort to increase students' understanding when the non-fiction text material for Indonesian language lessons theme 5 uses Sway Office 365 media? This study uses classroom action with the result that there is an increase in teacher and student activity so that the impact on student learning outcomes has increased from cycle I to cycle II, namely, cycle I (70.96%), and cycle II (93.55%). The conclusion of this study is that Sway Office 365 media can have a positive effect on online student learning activities and outcomes.